Social-emotional model of internet addiction - Savci, Mustafa; Aysan, Ferda (Aves, 2017)
Objective: The purpose of this study is to test the social-emotional model of internet addiction which was built by considering theoretical explanations and study results. For this general purpose, the following hypotheses have been tested: willingness to self-censor significantly, positively, and directly affects social anxiety, self-monitoring significantly, negatively, and directly affects social anxiety, social anxiety significantly, positively, and directly affects negative affection, negative affection significantly, positively, and directly affects daily internet use duration and internet addiction, daily internet use duration significantly, positively, and directly affects internet addiction. Methods: The social-emotional model of internet addiction was applied on 330 university students. The Revised Self-Monitoring Scale, Willingness to Self-censor Scale, Social Anxiety Scale for Adolescents, Positive and Negative Affect Scale, Young Internet Addiction Test-Short Form, and Personal Information Form were used as data collection instruments. The covariance matrix and Maximum Likelihood method were conducted in testing the model. Results: As a result of the analysis suggested hypotheses were confirmed and the proposed hypothetical model showed good fit [(chi(2) = 100.435, df = 25,chi(2)/df = 4.017, RMSEA = 0.096, GFI = 0.94, AGFI = 0.90, CFI = 0.94, IFI = 0.94, TLI (NNFI) = 0.91)]. Conclusion: Willingness to self-censor and unable to self-monitoring causes social anxiety. Social anxiety increases negative affect. Negative affection causes Internet addiction through daily Internet use duration. Negative affection and the daily Internet use duration directly affect Internet
Keywords: Internet addiction; negative affection; social anxiety; self-monitoring; willingness to self-censor